MESIN PENCACAH PAKAN TERNAK (STUDI KASUS: KELOMPOK PETERNAK KAMBING DI DESA JAGANSARI, KEC. GUBUG, KAB. GROBOGAN, JAWA TENGAH) - Jesica Putri Agustina; Fauzi Yusuf; Komala Setya Ramadhan; Lintang Anggraeni; Rieska Ernawati (Jurnal Riset Multidisiplin Edukasi, 2026)
The Goat Farmer Group in Jagansari Village still carries out the process of chopping animal feed manually using a sickle. This process requires relatively more time, produces non-uniform chopping results, and poses occupational safety risks due to bent working posture and the potential for cutting injuries. This study aims to design a livestock feed chopping machine that meets the needs of small-scale farmers using a Product Design and Development approach, incorporating Ergonomics, Safety, and Engineering Economics Analysis. The Quality Function Deployment (QFD) method is used to translate user needs into technical specifications of the machine. Ergonomic analysis is conducted using operator anthropometric data, while occupational safety aspects are analyzed using Job Safety Analysis (JSA). Economic feasibility is evaluated based on product profitability up to its selling price. The results show that the designed machine is more ergonomic, safer, and economically feasible for implementation among small-scale goat farmers.